Etude microbiologique préliminaire et cycle de développement chez les femelles de ver marin (annélide, polychète) genre Ophelia (savigni, 1822), vivante au niveau de la zone intertidale de la plage Sidi -mejdoub - Bouaza, djounaida; Dani, Zahia (My University, 2024)
This study focuses on some ecological and microbiological traits of the annelid Ophelia sp from the sandy intertidal zone of the Mostaganem coast. To this end, 75 adult female marine worms, genus Ophelia sp, were sampled at the Sidi-mejdoub station over a 5-month period starting in February 2024. Monthly monitoring of oocyte development shows an increase in oocyte diameter in March, which continues into the summer season. Abiotic factors remain important parameters for reproduction. The annelid population size class ranges from [25.00-58.00 mm [ relative growth is allometric: w = 0.0075 x1.1256 .the group projection shows a dispersion of Ophelia sp individuals in five (05) groups with three multimodal age classes within the population, which probably explains an active complex within the biotope. Microbiological analysis shows the presence of Gram+ , spore-forming bacteria "coccus, diplococcus" in association with the Ophelia worm. Key
Keywords: Sidi-mejdoube beach; Ophelia; ovocyte diameter; population dynamics; coccus